Surveying instrumental observations of displacement of mine workings contours - Nazarenko, V. O.; Brui, H. V.; Kuchin, O.; Mamuzić, I.; Назаренко, В. О.; Бруй, Г. В. (Hrvatsko metalurško društvo, 2025)
Maintenance and accident-free operation of underground mine workings in difficult mining and geological conditions, which are characterized by unstable, watered rocks, is provided by the use of anchor and frame anchor supports. Periodic leveling of the reference points and anchors of the support provides information about displacements in separate sections of mine workings at different time intervals and in different areas. Measurements were made in the pumping drift at a depth of 300 m. Mine length is 2550 m, average inclination angle is 4 º, еxcavation cross-section S=14,6 m2. The excavation is secured by rows of anchors with a step of 0,6-0,8 m.
Keywords: mines; mine maintainance; instrumental observations